2011
DOI: 10.1002/chem.201002297
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the cis‐Oxo‐Labile Binding Site Motif of Non‐Heme Iron Oxygenases: Water Exchange and Oxidation Reactivity of a Non‐Heme Iron(IV)‐Oxo Compound Bearing a Tripodal Tetradentate Ligand

Abstract: The spectroscopic and chemical characterization of a new synthetic non-heme iron(IV)-oxo species [Fe IV (O)( Me,H Pytacn)(S)] 2+ (2, Me,H Pytacn = 1-(2′-pyridylmethyl)-4,7-dimethyl-1,4,7-triazacyclononane, S = CH 3 CN or H 2 O) is described. 2 has been prepared by reaction of [Fe II (CF 3 SO 3 ) 2 ( Me,H Pytacn)] (1) with peracetic acid. Complex 2 bears a tetradentate N 4 ligand that leaves two cis-sites available for binding an oxo group and a second external ligand but, unlike related iron(IV)-oxo of tetrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 124 publications
11
114
0
Order By: Relevance
“…does not undergo protonation of the oxo ligand even at pH % 1, [15] indicating that the corresponding pK a < 1. These values show that in an analogous chemical environment, the Mn IV =O unit is at least 7 pKa units more basic than Fe IV =O.…”
Section: IVmentioning
confidence: 98%
“…does not undergo protonation of the oxo ligand even at pH % 1, [15] indicating that the corresponding pK a < 1. These values show that in an analogous chemical environment, the Mn IV =O unit is at least 7 pKa units more basic than Fe IV =O.…”
Section: IVmentioning
confidence: 98%
“…Note that this is in agreement with the previous results obtained by Mçssbauer spectroscopy. [17] Thee xpected Fe = Os tretch is predicted in the computed spectra of 3 2+ in frozen acetonitrile solution (831 cm À1 ). [17] Theexperimentally determined Fe = Os tretches of iron(IV) complexes in condensed phase expand from 780 to 900 cm À1 and as pin correlation with the spin state cannot be established.…”
Section: )]mentioning
confidence: 99%
“…[17] Thee xpected Fe = Os tretch is predicted in the computed spectra of 3 2+ in frozen acetonitrile solution (831 cm À1 ). [17] Theexperimentally determined Fe = Os tretches of iron(IV) complexes in condensed phase expand from 780 to 900 cm À1 and as pin correlation with the spin state cannot be established. [24] TheI RPD spectra do not give strong evidence for which isomers are formed.…”
Section: )]mentioning
confidence: 99%
See 1 more Smart Citation
“…Mössbauer spectroscopy has demonstrated that this reaction sequence leads to the generation of triplet state iron(IV) complexes ( S =1) 17. Using electrospray ionization (ESI) we were able to transfer the [(PyTACN)Fe(O)(OTf)] + ions to the gas phase and on addition of HNO 3 , the [(PyTACN)Fe(O)(NO 3 )] + ions ( m / z  382) were also detected (Figure S5 in the Supporting Information).…”
mentioning
confidence: 99%